Kinetic finite element model to optimize sulfur vulcanization: Application to extruded epdm weather‐strips. Issue 2 (20th July 2012) - Milani, G.; Milani, F.
Abstract A numerical two‐phase approach based on experimental scorch curve data fitting, to predict the optimal exposure time and cure temperature of extruded thick items is applied for the study of a real weather‐strip. In the first phase, an existing single equation kinetic model is used to predict the crosslinking density under sulfur vulcanization at variable temperatures. The model requires the calibration of only three kinetic constants. The variation with respect to temperature of such parameters is then evaluated by means of two experimental cure curves performed at two different temperatures. In the second phase, kinetic reaction parameters are implemented in finite element software, to perform thermal analyses on an extruded weather‐strip. Once evaluated the final mechanical properties of the item point by point, a set of compression tests is numerically simulated, assuming that the rubber behaves as a Mooney–Rivlin material under the large deformations. Elastic properties of the item are evaluated as a function of the vulcanization degree evaluated in the second phase. It is found that suboptimal vulcanizations result into lower elastic moduli and hence great deformability, sometimes incompatible with real scale engineering applications. POLYM. ENG. SCI., 2013. © 2012 Society of Plastics Engineers